2012
DOI: 10.1111/j.1365-2966.2011.20363.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution stage and massive disc of the interacting binary V 393 Scorpii

Abstract: V 393 Scorpii is a bright Galactic Double Periodic Variable showing a long photometric cycle of ≈253 d. We present new VIJK photometric time series for V 393 Scorpii along with the analysis of All Sky Automated Survey (ASAS) V-band photometry. We disentangled all light curves into the orbital and long-cycle components. The ASAS V-band orbital light curve was modelled with two stellar components plus a circumprimary optically thick disc assuming a semi-detached configuration. We present the results of this calc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…We separated multiperiodic V, I, J, and K light curves with a Fourier decomposition technique (for more details see Demircan 1979;Mennickent et al 2012a) and found two main Fourier components of frequencies f 1 and f 2 , the sum of which (including their most important harmonics) is the best representation of the light curves. f 1 is higher and associated with a period of 6.083299 d, which represents the orbital variability of the binary (see Fig.…”
Section: Orbital and Long Light Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…We separated multiperiodic V, I, J, and K light curves with a Fourier decomposition technique (for more details see Demircan 1979;Mennickent et al 2012a) and found two main Fourier components of frequencies f 1 and f 2 , the sum of which (including their most important harmonics) is the best representation of the light curves. f 1 is higher and associated with a period of 6.083299 d, which represents the orbital variability of the binary (see Fig.…”
Section: Orbital and Long Light Curvesmentioning
confidence: 99%
“…At present, there are more than 150 DPVs discovered in the Magellanic Clouds and 11 systems (including DQ Vel) in the Milky Way (Mennickent et al 2012a). Results of multiwavelength spectroscopy and/or photometry have made it possible to study DPVs in more detail, such as AU Mon (Desmet et al 2010;Djurašević et al 2010), V393 Sco (Mennickent et al , 2012a, and LP Ara (Mennickent et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We find that HD 170882 shows spectroscopic properties similar to other DPVs like AU Monocerotis, V 393 Scorpii, DQ Velorum and OGLE 05155332-6925581 (Mennickent et al, 2008, 2012a, 2012b, Barría et al 2013, Garrido et al 2013. These properties include the existence of an optically thick disc surrounding a B-type star and evidence for stream-disc interaction.…”
Section: Discussionmentioning
confidence: 62%
“…We noticed that the ASAS period (16.8599 days) does not fit the periodogram minimum as well as our period, probably because of the automatic character of the period searching algorithm used in this catalogue and the lack of filtering of bad data points. The light curve was disentangled with these two periods using the software written by Zbigniew Kołaczkowski and described in Mennickent et al (2012a). Afterwards, the resulting disentangled light curves were folded with both periods as shown in Fig.…”
Section: Photometric Ephemeridesmentioning
confidence: 99%
See 1 more Smart Citation